Apocalypse and Reform from Late Antiquity to the Middle Ages
1 online resource (244 pages)
Keywords: Apocalypse and Reform from Late Antiquity to the Middle Ages provides a range of perspectives on what reformist apocalypticism meant for the formation of Medieval Europe, from the Fall of Rome to the twelfth century. It explores and challenges accepted narratives about both the development of apocalyptic thought and the way it intersected with cultures of reform to influence major transformations in the medieval world. Bringing together a wealth of knowledge from academics in Britain, Europe and the USA this book offers the latest scholarship in apocalypse studies. It consolidates a paradigm shift, away from seeing apocalypse as a radical force for a suppressed minority, and towards a fuller understanding of apocalypse as a mainstream cultural force in history. Together, the chapters and case studies capture and contextualise the variety of ideas present across Europe in the Middle Ages and set out points for further comparative study of apocalypse across time and space. Offering new perspectives on what ideas of ‘reform’ and ‘apocalypse’ meant in Medieval Europe, Apocalypse and Reform from Late Antiquity to the Middle Ages provides students with the ideal introduction to the study of apocalypse during this period.